Intersectorality, interdisciplinarity and health education: question of university social responsibility - Sánchez Sanabria, Marina; Romero Daza, Angélica; Hernández Salas, Nancy (Universidad y Salud, 2015)
The objective of this article of reflection was to point out the value of the intersectorality, interdisciplinarity and health education as pillars to develop a University social responsibility model founded on social awareness and culture of the value of otherness. It comes from the results of the research made about the perception of risks the inhabitants of greater vulnerability of the urban area of Valledupar take who have life styles that can be modelled through empowerment and healthy well-being to develop the capacity for self-management to improve living conditions. It can be concluded that it is required to have a greater institutional presence that enhances State and private efforts, where the University has a strong commitment to promote projects with relevance and social awareness.